1996
DOI: 10.1007/bf00049246
|View full text |Cite
|
Sign up to set email alerts
|

Oblique diffraction of surface waves by a submerged vertical plate

Abstract: A train of small-amplitude surface waves is obliquely incident on a fixed, thin, vertical plate submerged in deep water. The plate is infinitely long in the horizontal direction. An appropriate one-term Galerldn approximation is employed to calculate very accurate upper and lower bounds for the reflection and transmission coefficients for any angle of incidence and any wave number thereby producing very accurate numerical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 17 publications
3
0
0
Order By: Relevance
“…Their averages give actual values of reflection coefficients for all practical purposes. The present method produces numerical results which are in good agreement with the earlier results obtained by [22].…”
Section: Oblique Scattering By a Thin Vertical Platesupporting
confidence: 89%
See 2 more Smart Citations
“…Their averages give actual values of reflection coefficients for all practical purposes. The present method produces numerical results which are in good agreement with the earlier results obtained by [22].…”
Section: Oblique Scattering By a Thin Vertical Platesupporting
confidence: 89%
“…6 and 7 of [22]. Further it is also observed that for most of the cases the results displayed in Table 5 coincide upto 3 to 4 decimal places with the results in Table 1 of [22]. These provide another check on the correctness of the results obtained using the present method.…”
Section: Oblique Scattering By a Thin Vertical Platesupporting
confidence: 74%
See 1 more Smart Citation